2008
DOI: 10.1074/jbc.m709185200
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Interaction of 14-3-3 Proteins with the ERK1/2 Scaffold KSR1 Occurs in an Isoform-specific Manner

Abstract: Identifying 14-3-3 isoform-specific substrates and functions may be of broad relevance to cell signaling research because of the key role played by this family of proteins in many vital processes. A multitude of ligands have been identified, but the extent to which they are isoform-specific is a matter of debate. Herein we demonstrate, both in vitro and in vivo, a specific, functionally relevant interaction of human 14-3-3␥ with the molecular scaffold KSR1, which is mediated by the C-terminal stretch of 14-3-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 49 publications
1
30
1
Order By: Relevance
“…However, only 14-3-3␥, but neither 14-3-3␤ nor 14-3-3, could bind RapE63. Similarly, only 14-3-3␥, but neither 14-3-3␤ nor 14-3-3, can bind KSR (45). This is consistent with the contribution of KSR to 14-3-3 binding to phosphorylated Rap1.…”
Section: Ksr Is Required For B-raf To Bind Rap1 and Signal To Erks-supporting
confidence: 75%
See 1 more Smart Citation
“…However, only 14-3-3␥, but neither 14-3-3␤ nor 14-3-3, could bind RapE63. Similarly, only 14-3-3␥, but neither 14-3-3␤ nor 14-3-3, can bind KSR (45). This is consistent with the contribution of KSR to 14-3-3 binding to phosphorylated Rap1.…”
Section: Ksr Is Required For B-raf To Bind Rap1 and Signal To Erks-supporting
confidence: 75%
“…5C). It has been shown that KSR binds selectively to 14-3-3␥, but not 14-3-3␤ or 14-3-3 (45). Only 14-3-3␥, but neither 14-3-3␤ nor 14-3-3, could bind RapE63 (Fig.…”
Section: -3-3 Binding To Rap1mentioning
confidence: 99%
“…20 The Lys50 residue is located on the charged face of the binding groove (together with Arg57, Arg61, Arg132, and Tyr133) ( Figure 1) and is essential for ligand binding. [61][62][63] All four subjects (B and D-F) from this study are females with seizure onset in the first year of life, although a precise age of onset for subject F is unknown. Subjects B, E, and F have the same mutation and similar epilepsy phenotype, which includes generalized epilepsy with myoclonic, (atypical) absence, and generalized tonic-clonic (GTC) seizures.…”
mentioning
confidence: 99%
“…Isoformspecific functions of 14-3-3 proteins are difficult to explain, because these molecules share a high degree of structural homology, particularly in their binding regions. Nevertheless, some studies have begun to clarify the structural basis for their specific roles (20,62). Mouse transgenic approaches provide an important tool with which to define the different roles of 14-3-3 isoforms in vivo while awaiting additional insights from structural studies.…”
Section: Discussionmentioning
confidence: 99%
“…(g to i) Expression of 14-3-3ε (green), examined by immunofluorescence staining on frozen E18.5 sections. (48) 23 (20) a No significant differences between the genotypes are evident.…”
Section: -3-3 Is Expressed In the Developing Mouse Heart And Embryomentioning
confidence: 99%